APPLICATION OF MARKOV CHAIN PROCESS IN FORCASTING THE ADOPTION OF AN OIL PALM SEED TECHNOLOGY IN NIGERIA. - ONYENWAKU , C. E.; ALARMS, L. D. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Attempts have been made in this study to project the future adoption trends of an improved oil palm seed variety in Nigeria, using a first order Markov chain process. Farmers were classified into six different adoption categories based on the percentage of their total cultivated land under the improved seed variety during the 1982 and 1983 planting seasons. The results show that the adoption rate will be 48 percent in 1985 and involve 14,906 farmers in varying degrees. By 1995, the adoption index is predicted to reach 70.6 percent and will involve 20,474 farmers.